Piano Trio by Amanda Maier in the Context of Genre Evolution - Serdiuk, Yaroslava (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
The relevance of the study. The name of Swedish composer and violin virtuoso of the Romantic era Amanda Maier-Röntgen is virtually unknown in Ukrainian musicology. Her work was forgotten for long time and rediscovered by European (particulary Swedish) and American musicians. But at one time she was the first woman who received the title of “Musik Direktor” after graduating from the Royal Academy of Music in Stockholm. She also perfected her performing and composing mastership in Leipzig, her work was praised by critics and leading European musicians: E. Grieg, J. Brahms, K. Schumann, with whom A. Maier maintained creative contacts. Existing research in European and American musicology considers basically only biography and performing activity of A. Maier, not her composer style or genre-stylistic and compositional features of her works. The main objective of the research is to consider the stylistic parameters in chamber music works by A. Maier, in particular, her interpretation of the piano trio genre. The methodology of the study is based on the main methods of music science: compositional, harmonic, polyphonic, intonation genre-stylistic analysis, historical-comparative method. The main findings and conclusions of the study. The Trio in E flat major by A. Maier embodies both the most characteristic features of this genre that have developed in the works of classical composers, and the achievements of Romantic composers of the Austrian-German school of the first half of the nineteenth century, and the latter have priority in this work. Continuity with classical traditions can be traced in the four-part structure of the cycle, which has become typical for the trio genre, beginning with the works by L. van Beethoven; in specific techniques of ensemble writing (unison presentation of the initial theme with all instruments, dialogicity — comparison of the sound of ensemble tutti and solo piano; elements of imitation in strings part; polyphonic work with themes in development). Fundamental role of lyrics, reliance on the song and romance intonations, the kinship of themes within each of the parts, end-to-end thematic development, and thematic arches between the movements in composer thinking of A. Maier comes from Romanticism. Among the individual features inherent in the Trio A. Maier — laconic composition, plasticity of melodic lines, exceptional fluidity and coherence of form, which is achieved due to intonational similarity of the themes, openness of the syntactic structures or veiling of the cadences, organicity of the modulation transitions; dynamism of the developing sections. Also, some melodic and harmonic elements of the Trio (for example, in the themes of the middle sections of Scherzo and Andante) hint at the Scandinavian national folklore. Amanda Mayer's trio represents the best achievements of the romantic stage in the evolution of the genre: your embodiment of classical traditions together with the disclosure of personal lyrical and psychological content.